2009
DOI: 10.1088/1758-5082/1/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

A Lindenmayer system-based approach for the design of nutrient delivery networks in tissue constructs

Abstract: Large thick tissue constructs have reported limited success primarily due to the inability of cells to survive deep within the scaffold. Without access to adequate nutrients, cells placed deep within the tissue construct will die out, leading to non-uniform tissue regeneration. Currently, there is a necessity to design nutrient conduit networks within the tissue construct to enable cells to survive in the matrix. However, the design of complex networks within a tissue construct is challenging. In this paper, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…We have used PEGDA to generate 3D scaffolds in our research [ 7 ]. Several PEGDA hydrogel scaffolds have been developed for the reconstruction of injured hard and soft tissues, although the in vivo performances have not been reported yet [ 8 , 9 ]. The reason for using PEGDA in our research over other materials is that a thin layer of PEGDA membrane can be manufactured readily to allow for cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…We have used PEGDA to generate 3D scaffolds in our research [ 7 ]. Several PEGDA hydrogel scaffolds have been developed for the reconstruction of injured hard and soft tissues, although the in vivo performances have not been reported yet [ 8 , 9 ]. The reason for using PEGDA in our research over other materials is that a thin layer of PEGDA membrane can be manufactured readily to allow for cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several engineered tissue grafts have been developed for the reconstruction of the injured hard and soft tissues [ 3 ]. Yasar et al [ 4 ] used Lindenmayer systems, an elegant fractal-based language algorithm framework, in designing vasculature networks that could potentially be incorporated in hydrogel scaffolds like PEGDA. The reason for using PEGDA over other materials is that PEGDA is 3D networked structures that can be manufactured easily to allow for the cell growth at higher depth using photolithograph process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to be a valid method to manufacture multiple-layer scaffolds for allowing the constructions of channels within the scaffold to better distribute nutrients to the cells. Yasar et al [ 4 ] study also found that Polyethylene Glycol Diacrylate (PEGDA) tissue scaffolds having thickness higher than 1 mm were shown to have limited applications as a three-dimensional cell culture device due to the inability of cells to survive within the scaffolds. Without access to adequate nutrients, cells placed deep within the PEGDA tissue construct having thickness higher than 1 mm die out, leading to nonuniform tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of scaffolds can also be adjusted according to numerically generated models to meet the desired requirements. 18 Porosity patterns can be generated by using design-based methods 19 and/or fabrication-based methods 20 either by simple repetition of predetermined subunits 21 or generated by means of mathematical models developed by analysis of the target tissue structure 22,23 (Fig. 2).…”
Section: Design By Replication Of Real Tissue Modelsmentioning
confidence: 99%